Ethics and multinational corporations vis-à-vis developing nations - Simpson, James R. (Journal of business ethics, 1982)
The ethical dilemma of large-scale multinational corporations is presented. The list of complaints and issues is summarized. A case is made for the concept of multinationals being inherently beneficial in today's world of high technology and dependence on international trade. The difficulty is extreme power wielded by some groups. It is concluded that a philosophical ideal is for control on size and power as well as international rules to prevent abuses of power. The concern is that today the worthiness of being relatively small is slowly but surely being eroded.